2021
DOI: 10.1001/jamanetworkopen.2021.21122
|View full text |Cite
|
Sign up to set email alerts
|

Association of Social Support With Brain Volume and Cognition

Abstract: IMPORTANCE Cognitive resilience refers to the general capacity of cognitive processes to be less susceptible to differences in brain structure from age-and disease-related changes. Studies suggest that supportive social networks reduce Alzheimer disease and related disorder (ADRD) risk by enhancing cognitive resilience, but data on specific social support mechanisms are sparse. OBJECTIVE To examine the association of individual forms of social support with a global neuroanatomical measure of early ADRD vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 68 publications
4
22
1
Order By: Relevance
“…To characterize age differences in the association of loneliness with dementia risk, the primary dementia analysis was performed for the entire sample and stratified by age group: <80 and ≥80 years of age. The decision to characterize age differences by stratifying the sample at 80 years of age was made a priori and based on knowledge of extant literature reporting associations of loneliness with greater cortical amyloid and regional tau accumulation using PET imaging, 14,15 previous FS investigations suggesting that loneliness-related dementia risk 10,39 and risk of neurocognitive markers of early ADRD vulnerability 42 varied between younger and older adults, and loneliness prevalence estimates demonstrating a slight increase by age for young-old adults (age 65-79 years) and a more notable increase for oldest-old adults ≥80 years of age. 43 For the primary dementia analysis, overall and by age, Cox proportional hazards regression models estimated age-, sex-, and education-adjusted hazard ratios for 10-year dementia risk comparing participants who were lonely with those who were not lonely.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize age differences in the association of loneliness with dementia risk, the primary dementia analysis was performed for the entire sample and stratified by age group: <80 and ≥80 years of age. The decision to characterize age differences by stratifying the sample at 80 years of age was made a priori and based on knowledge of extant literature reporting associations of loneliness with greater cortical amyloid and regional tau accumulation using PET imaging, 14,15 previous FS investigations suggesting that loneliness-related dementia risk 10,39 and risk of neurocognitive markers of early ADRD vulnerability 42 varied between younger and older adults, and loneliness prevalence estimates demonstrating a slight increase by age for young-old adults (age 65-79 years) and a more notable increase for oldest-old adults ≥80 years of age. 43 For the primary dementia analysis, overall and by age, Cox proportional hazards regression models estimated age-, sex-, and education-adjusted hazard ratios for 10-year dementia risk comparing participants who were lonely with those who were not lonely.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive resilience was defined as the modification of total cerebral volume's association with cognition. The results showed that social support in the form of supportive listening was associated with greater cognitive resilience, independently modifying the association between lower total cerebral volume and poorer cognitive function that would otherwise indicate increased AD vulnerability at the preclinical stage [432].…”
Section: Social Engagementmentioning
confidence: 93%
“…Therefore, CBT may be a useful in normalizing the structural and functional changes associated with mental health disorders [ 64 , 65 ] or following childhood trauma. Similarly, psychotherapies [ 66 , 67 ] and evidence-based treatment [ 68 ] led to observable functional and structural changes in depressed patients and a positive relationship between total cerebral volume and availability of ‘supportive listening’ in depressed adults was observed [ 69 ]. Potentially, treatment options targeting the neurobiological differences identified in this cohort could be used preventatively following trauma.…”
Section: Discussionmentioning
confidence: 99%